Memorialization in Germany since 1945 - Niven, William John (2010)
"Memorialization in Germany since 1945 provides a wide-ranging discussion of contemporary Germany's rich memorial landscape. It discusses the many memorials to German losses during the Second World War, to the victims of national socialism, and to those of GDR socialism. With up-to-date coverage of many less well-known memorials as well as the most publicised ones"–Provided by publisher